Electrodiagnostic evaluation and treatment of root avulsion in an obstetric brachial plexus injury case report [Doǧumsal brakiyal pleksus yaralanmalarında kök avülsiyonunun elektrodiyagnostik i̇ncelemesi ve tedavisi-olgu sunumu] - (:unkn) unknown (Marmara University, 2011)
Obstetrical brachial plexus palsy is a common peripheral nerve injury in childhood. Root avulsion is one of the poor prognostic factors. The role of nerve conduction study and electroneuromyography (ENMG) is to differentiate root avulsion from plexus lesions. Despite the normal sensory nerve conduction study, the absence of motor nerve conduction is diagnostic of root avulsion. Because of the root avulsion, definitely establish surgical decision and time of surgery, in the presence of doubt electrodiagnostic studies should be made. In this case, to emphasize the role of electroneuromyography, we presented a 5-month old male patient who was referred to our electrophysiology laboratory with the prediagnosis of brachial plexus injury.
Keywords: Electromyography; Obstetrical brachial plexus palsy; Root avulsion